Cyclic AMP Pathway Activation and Extracellular Zinc Induce Rapid Intracellular Zinc Mobilization in Candida albicans - Kjellerup, Lasse; Winther, Anne-Marie L.; Wilson, Duncan; Fuglsang, Anja T. (Frontiers in Microbiology, 2018)
Zinc is an essential micronutrient, required for a range of zinc dependent enzymes and transcription factors. In mammalian cells, zinc serves as a second messenger molecule. However, a role for zinc in signaling has not yet been established in the fungal kingdom. Here, we used the intracellular zinc reporter, zinbo 5, which allowed visualization of zinc in the endoplasmic reticulum and other components of the internal membrane system in Candida albicans. We provide evidence for a link between cyclic AMP/PKA- and zinc- signaling in this major human fungal pathogen. Glucose stimulation, which triggers a cyclic AMP spike in this fungus resulted in rapid intracellular zinc mobilization and this “zinc flux” could be stimulated with phosphodiesterase inhibitors and blocked via inhibition of adenylate cyclase or PKA. A similar mobilization of intracellular zinc was generated by stimulation of cells with extracellular zinc and this effect could be reversed with the chelator EDTA. However zinc-induced zinc flux was found to be cyclic AMP independent. In summary, we show that activation of the cyclic AMP/PKA pathway triggers intracellular zinc mobilization in a fungus. To our knowledge, this is the first described link between cyclic AMP signaling and zinc homeostasis in a human fungal pathogen.